1851 census, Canada West (Central Microfilm Unit, Public Archives of Canada, 1969)
Census volumes consist of two parts, a personal census and an agricultural census. Personal census has columns for names, professions, place of birth, religion, age, sex, marital status, race, members of household, deaf and other handicaps, births, deaths, type of buildings, information on businesses, etc. Agricultural census has columns for names, concession, no. of acres of land, type of crops, etc.